أبعاد المُخَطَّطات الصُّوريَّة في القُرآن الكريم -سورة طه نموذجًا- - شريف, أ.م.د. نيان عثمان (Sulaimani Journal for Humanities, 2023)
The Cognitive Linguistics school, since its inception, has been concerned with the human mental aspect to determine the depth of semantics. This interest in the mental process is demonstrated through the development of many theories in cognitive linguistics in general and cognitive semantics in particular. One of these theories is the theory of image schemas, which appeared in the early twentieth century in the work of (J. Piaget) and (F. C. Bartlett). Some scholars argue that the concept of image schemas is ancient, with its origins dating back to the work of (I. Kant) in the eighteenth century, but the works of (Bartlett) represent the basis of this theory. (M. Johnson) and (G. Lakoff) together coined the term image schema in their books (1987). The theory of image schemas is the process of recalling the mind to the abstract physical image through one of the senses, then comes the process of linking the physical image with the image that is required to be known to determine the intended image. There are several types of image schemas, including: link schema, containment schema, part and whole schema, balance schema, path schema (source, path and goal), cycle schema, force schema, motor schemata, center and periphery schema. This theory, like other theories in the field of cognitive, works on the analysis of texts and discourse of all kinds, in order to clarify the meaning in the most accurate way. Therefore, this theory came as an attempt to explain the Qur’anic discourse (the discourse in Surat Taha), with an explanation of schemas types, their elements and foundations in the discourse analysis.
Keywords: Keywords: Image schemes; Quranic discourse; link scheme; containment scheme; and balance scheme